Integrating Islamic Values into School Counseling Programs: Preventive Interventions for Adolescent Mental Health in Muslim-Majority Contexts - Betsi Siti Nurhidayah (Sekolah Tinggi Agama Islam Kuningan, 2025)
Adolescent mental health challenges continue to rise globally, requiring culturally grounded preventive interventions, especially in Muslim-majority educational contexts. Islamic values are deeply embedded in students’ daily lives, yet school counseling programs often lack structured religious integration. This study aims to identify Islamic psychological constructs relevant to preventive counseling, examine their implementation in school settings, and analyze their impact on students’ emotional and behavioral adjustment. Using a qualitative descriptive design, data were collected through semi-structured interviews, non-participant observations of counseling sessions, and document analysis involving school counselors, Islamic education teachers, and administrators selected through purposive sampling. Thematic analysis revealed that core Islamic constructs—such as sabr, shukr, tawakkul, muhasabah, and akhlaq—were consistently integrated into counseling practices through value-based psychoeducation, spiritually guided emotional regulation training, family–school collaboration, and peer-support circles rooted in Islamic ethics. These interventions significantly improved students’ emotional regulation, reduced behavioral conflicts, and increased help-seeking behavior. Stakeholders expressed strong support for the culturally aligned model but emphasized the need for structured guidelines and counselor training. The study concludes that integrating Islamic values strengthens the preventive function of school counseling and enhances its cultural relevance, offering practical implications for policy development, counselor preparation, and holistic student well-being.